Hubungan Antara Kadar Kolesterol Dalam Darah dengan Kejadian Hipertensi Pada Lansia di Pkm Tabongo Kabupaten Gorontalo - Iqbal Febrianto Lesar; Dewi Modjo; Andi Akifa Sudirman (Jurnal Medika Nusantara, 2023)
Hypertension is a non-communicable disease which is a problem in the health sector and is often found in primary health care facilities. Based on data from the Gorontalo District Health Office for 2021, hypertension ranks first, with 16,999 cases. Hypertension sufferers in the elderly ?60 years, namely 6,566 people with the highest order being at the Tabongo Health Center with a total number of hypertension sufferers of 1,371 people. This study uses a descriptive quantitative research design with an analytic cross sectional study approach. The population in this study were all elderly people with hypertension in October 2022 with a total of 108 elderly people aged 60-90 years, both men and women at the Tabongo Health Center, Gorontalo Regency. Determination of the sample size was carried out using the Slovin formula, namely as many as 52 respondents. The data obtained were then analyzed univariately and bivariately using the Chi-Square test. The results showed that based on the results of the Chi-Square test, a Sig (2-sided) value of 0.021 was obtained, which means that Ho was rejected and Ha was accepted. So it can be concluded that there is a relationship between cholesterol levels in the blood and the incidence of hypertension in the elderly at the Tabongo Health Center, Gorontalo Regency.